2013
DOI: 10.1111/epi.12255
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind and epilepsy: What clinical implications?

Abstract: Summary Purpose Epilepsy can impair theory of mind (ToM), but the clinical significance of such a deficit is unknown. This study evaluated the influence of selective ToM deficits on self‐appraisal, coping, and quality of life (QoL) in patients with focal epilepsy. Methods Data were collected from 66 patients with temporal or frontal lobe epilepsy, and from 42 healthy controls. The Faux Pas Task (FPT), Multiple Ability Self‐report Questionnaire (MASQ), Coping Responses Inventory‐Adult (CRI‐Adult), and World Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
57
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 36 publications
13
57
1
1
Order By: Relevance
“…An impaired capacity to understand mental states and to comprehend interpersonal relations could affect self-appraisal and adaptation capacities in subjects with OCD. 51 In agreement with a study by Giovagnoli et al, 52 we support the idea that mentalizing ability deficits predict self-rated cognitive functioning, strategies for coping with stressful events, and overall quality of life perception. The mentalizing ability deficit in OCD may have psycho-behavioral implications.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An impaired capacity to understand mental states and to comprehend interpersonal relations could affect self-appraisal and adaptation capacities in subjects with OCD. 51 In agreement with a study by Giovagnoli et al, 52 we support the idea that mentalizing ability deficits predict self-rated cognitive functioning, strategies for coping with stressful events, and overall quality of life perception. The mentalizing ability deficit in OCD may have psycho-behavioral implications.…”
Section: Discussionsupporting
confidence: 91%
“…53 Adequate comprehension of real mental states and interpersonal dynamics could help one avoid redundant thoughts or actions, make behavior fluid, or enhance feelings of belonging to a social group. 52 Several studies have shown that the association between ToM and psycho-behavioral alterations may reflect damage to common neural substrates that underlie ToM and emotional-behavioral control. 53,54 Regarding experiencesharing measures, OCD subjects did not differ from controls in the experience-sharing dimension (affective empathy) when other people expressed emotions with positive valence.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a paucity of experimental research of social cognition at present in epilepsy populations, those so far document particular difficulties in emotional recognition and theory of mind [56][57][58][59][60][61][62][63][64][65][66] in temporal lobe epilepsy (TLE), frontal lobe epilepsy (FLE) and idiopathic generalised epilepsy (IGE), with the addition of prosodic recognition and self-ratings of empathy in patients with refractory mesial temporal lobe epilepsy (MTLE) [59]. These clinical groups make up over half of the epilepsy population and therefore further understanding of these difficulties is paramount.…”
Section: Understanding Why Difficulties Arise In Social Competence Inmentioning
confidence: 99%
“…Nevertheless, they provide important information as impairment in recognition of basic emotions is considered to be a prerequisite for ToM in ecological tasks [35] and in groups such as those with MTLE, ToM difficulties in some patients appear to be comparable to individuals with autism [59]. Furthermore, ToM is found to be the area that is most greatly associated with real life social functioning and community outcomes [67], self appraisal, coping and overall quality of life perception [57] and therefore is of significant clinical importance.…”
Section: Understanding Why Difficulties Arise In Social Competence Inmentioning
confidence: 99%
See 1 more Smart Citation